Investigating the behavior of individual foundations located on a clay embankment reinforced with geogrid and sand - Soha Arkavazi; Hassan Sharafi (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
The bearing capacity of surface foundations is one of the most important factors affecting the design of structures located on them. To improve the load-bearing capacity of surface foundations, the reinforcement method can be used by using geogrids in the soil under the foundation. In this research, we examine the advantages of using a replacement sand layer in clay slopes and also placing geogrid layers inside the replaced sand soil. In this article, using the PLAXIS finite element method, we have investigated the effect of various geometric parameters, including the thickness of the replaced sand layer, the number of geogrids, the distance of the highest geogrid to the floor under the foundation, the distance between geogrids and the length of geogrids. By determining the optimal value of each of the parameters, it is possible to make the best use of the geogrid as reinforcement and increase the carrying capacity as much as possible. Finally, the numerical results will be compared with the laboratory results to verify the accuracy.